2009
DOI: 10.1111/j.1365-2265.2009.03752.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood coagulation, fibrinolysis and lipid profile in patients with prolactinoma

Abstract: We found some important differences in the haemostatic parameters between the patients with prolactinoma and healthy controls. Increased platelet count, fibrinogen, PAI-1 and decreased TFPI in patients with prolactinoma may represent a potential hypercoagulable and hypofibrinolytic state, which might augment the risk for atherosclerotic and atherothrombotic complications. Thus, disturbances of the haemostatic system and dyslipidaemia may lead to the excess mortality in patients with prolactinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
56
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 42 publications
(47 reference statements)
5
56
1
Order By: Relevance
“…In particular, decreased HDL cholesterol and increased TC and triglycerides have been reported in patients with prolactinomas as compared to healthy control subjects [61,62,63,64]. Similarly, total body fat percentage has been demonstrated to be increased in newly diagnosed treatment-naive hyperprolactinemic patients when compared to controls [44].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, decreased HDL cholesterol and increased TC and triglycerides have been reported in patients with prolactinomas as compared to healthy control subjects [61,62,63,64]. Similarly, total body fat percentage has been demonstrated to be increased in newly diagnosed treatment-naive hyperprolactinemic patients when compared to controls [44].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, decreased HDL and increased CHOL and TG have been reported in patients with prolactinomas as compared to controls [75,76,77,78], and a direct correlation between lipid metabolism and PRL levels has been proposed [48]. PRL can directly act on adipose tissue and may be involved in the lipid metabolism of mature adipocytes [79,80,81,82]. Moreover, D 2 R is also expressed on human adipocytes, suggesting a regulatory role for peripheral dopamine in adipose functions [83].…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, while platelet count, fibrinogen, tissue plasminogen activator inhibitor-1 (PAI-1) were increasing, plasma tissue factor pathway inhibitor (TFPI) level was detected decreased. It was suggested that this condition might contribute to an increased risk of atherosclerotic and atherothrombotic complications (21).…”
Section: Discussionmentioning
confidence: 99%